Teacher Competency Improvement Efforts in the Preparation of Syllabus and Lesson Plans Through Ongoing Academic Supervision at SMP Negeri 6 Dumai - Effendi, Andi (Journal of Educational Sciences, 2023)
In teaching and learning activities, it always includes three main activities namely planning, implementation and evaluation. The same thing happened with the teaching and learning process at SMP Negeri 6 Dumai. A teacher is required to plan, implement and evaluate learning, the purpose of this research is to prove scientifically whether continuous academic supervision can increase teacher competence in preparing syllabus and lesson plans. Syllabus and lesson plans are the preparation of a teacher when he wants to teach. The research approach used in this study is a qualitative approach. Based on the results of the analysis for the 2020/2021 school year at SMP Negeri 6 Dumai. Continuous academic supervision has been scientifically proven to be able to increase teacher competence in preparing syllabus and lesson plans at SMP Negeri 6 Dumai. This is proven by the increase in the number of good teacher syllabuses from 38% to 82% after academic supervision. In addition, the number of good quality lesson plans also increased from 34% to 82%. The academic supervision generally can increase teacher competence in compiling syllabus and lesson plans.